Abnormal processing of emotional prosody in Williams syndrome: an event-related potentials study - Pinheiro, Ana P. (2011)
Williams syndrome (WS), a neurodevelopmental genetic disorder due to a microdeletion in chromosome 7, is described as displaying an intriguing socio-cognitive phenotype. Deficits in prosody production and comprehension have been consistently reported in behavioral studies. It remains, however, to be clarified the neurobiological processes underlying prosody processing in WS. This study aimed at characterizing the electrophysiological response to neutral, happy, and angry prosody in WS, and examining if this response was dependent on the semantic content of the utterance. A group of 12 participants (5 female and 7male), diagnosed with WS, with age range between 9 and 31 years, was compared with a group of typically developing participants, individually matched for chronological age, gender and laterality. After inspection of EEG artifacts, data from 9 participants with WS and 10 controls were included in ERP analyses. Participants were presented with neutral, positive and negative sentences, in two conditions: (1) with intelligible semantic and syntactic information; (2) with unintelligible semantic and syntactic information (‘pure prosody’ condition). They were asked to decide which emotion was underlying the auditory sentence. Atypical event-related potentials (ERP) components were related with prosodic processing (N100, P200, N300) in WS. In particular, reduced N100 was observed for prosody sentences with semantic content; more positive P200 for sentences with semantic content, in particular for happy and angry intonations; and reduced N300 for both types of sentence conditions. These findings suggest abnormalities in early auditory processing, indicating a bottomup contribution to the impairment in emotional prosody processing and comprehension. Also, at least for N100 and P200, they suggest the top-down contributions of semantic processes in the sensory processing of speech. This study showed, for the first time, that abnormalities in ERP measures of early auditory processing in WS are also present during the processing of emotional vocal information. This may represent a physiological signature of underlying impaired on-line language and socio-emotional processing.